Determinants of BI 7 – Days Reverse Repo Rate, GDP, and Exchange Rate Against the Money Supply - Tia Ichwani; Chaerani Nisa (Kusuma Negara Business School, 2021)
The size of a country's progress will always be seen from the economic growth in that country. No exception for developing countries such as Indonesia, economic growth will always be the centre of attention. In this era of globalization, the development of the money supply (both M1 and M2) in society is increasing and expanding. M1 implies money supply in a narrow sense, namely limited to currency and demand deposits, while M2 contains a fairly broad meaning or scope, namely savings, demand deposits, and foreign exchange. This study identifies BI-7 Days Repo Rate factors, national income (GDP), and an exchange rate that affects the money supply (M1).